A Feasibility Study on the Establishment of Angel’s Touch at Hobart Commercial Center, Zabarte Road, Novaliches, Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Angels Touch offers a body massage spa to offer for the customers who may want to be relaxed and to help people with disabilities to earn a living. The idea behind a body treatment is just as important services which are carried out in a simple atmosphere that disturbs the stress of the day. You feel free from everything and feel relaxed. The study adopted a descriptive and quantitative type of research. Detailed research instruments were developed and pretested before they were administered. The number of samples was 100 which stand as a variance for the general population; this variance was definitely obtainable and applicable for a statistical testing. The target population was a Schools, Market Stores, Commuters, Employees along Zabarte Novaliches Quezon City. The main instrument of the study was a survey questionnaires which were designed and administered. Other method that was used is the personal or (Face to Face) interview, which the response rate was usually high as the respondent typically found it difficult to refuse an interviewer face to face. The study adopted a descriptive and quantitative type of research. Detailed research instruments were developed and pretested before they were administered. The number of samples was 100 which stand as a variance for the general population; this variance was definitely obtainable and applicable fora statistical testing. The target population was a Schools, Market Stores, Commuters, Employees along Zabarte Novaliches Quezon City . The main instrument of the study was a survey questionnaires which were designed and administered. Other method that was used is the personal or (Face to Face) interview, which the response rate was usually high as the respondent typically found it difficult to refuse an interviewer face to face. Angel’s Spa choose to establish a body massage spa to offer the customers who may want to relax and to help the people with disabilities to earn a living. The idea behind a body treatment is just as important to cleanse, exfoliate, and hydrate the skin on your body as it is the skin of your face and you feel refreshed and rejuvenated with our services which are carried out in a simple atmosphere that disturbs the stress of the day. You feel free from everything and feel relaxed.
Keywords: massage spa